Association of Pre‐Chemotherapy Peripheral Blood Pro‐Inflammatory and Coagulation Factors with Physical Function in Women with Breast Cancer. (30th May 2017) - Yuan, Yuan; Vora, Nilesh; Sun, Can-Lan; Li, Daneng; Smith, David; Mortimer, Joanne; Luu, The-Hang; Somlo, George; Waisman, James; Chao, Joseph; Katheria, Vani; Synold, Timothy; et al.
Abstract: Background: Pro‐inflammatory and coagulation factors serve as biomarkers of aging and functional reserve. The purpose of this study was to determine if pro‐inflammatory (interleukin‐6 [IL‐6], C‐reactive protein [CRP]), and coagulation (D‐dimer) factors were associated with pre‐chemotherapy functional status in women with stage I–III breast cancer. Patients and Methods: Prior to chemotherapy initiation in patients with stage I–III breast cancer, the following was captured: IL‐6, CRP, D‐dimer blood levels, and physical function measures including activities of daily living (ADL, subscale of Medical Outcomes Study Physical Health); instrumental activities of daily living (IADL, subscale of the Older Americans Resources and Services Program); Timed Up and Go (TUG); physician‐rated Karnofsky Performance Status (KPS); and self‐rated KPS. The association of these biomarkers with physical function measures was evaluated. Results: One hundred sixty patients (mean age 58.3 years, range 30–81 years) with stage I–III breast cancer (stages I [ n = 34; 21.5%], II [ n = 88; 55.7%], III [ n = 36; 22.8%]) were enrolled. The group with poorest physical function (defined by ADL <70, IADL <14, and TUG ≥10 seconds) had higher levels of IL‐6 ( p = .05), D‐dimer ( p = .0004), and CRP ( p = .05). There was no significant association between these biomarkers and KPS. Patients with at least two biomarkers in the highest quartile were more likely to have poorer physical function (odds ration [OR] 18.75, p < .001). In multivariate analysis adjusting for age, stage, number of comorbidities, and body mass index, the association remained (OR 14.6, p = .002). Conclusion: Pre‐chemotherapy biomarkers of aging are associated with poorer physical function among patients with breast cancer across the aging spectrum. The Oncologist 2017;22:1189–1196 Abstract : Breast cancer is a disease associated with aging. Before initiation of chemotherapy, an assessment of functional reserve is needed; however, simple performance assessment scores may not reflect the diverse nature of physical function and risk of toxicity among older adults. The focus of this article is on understanding the association between pre‐chemotherapy biomarkers (IL‐6, CRP, and D‐dimer) and measures of physical function.